IMPLEMENTASI TUGAS POKOK DAN FUNGSI KEPALA URUSAN PEMERINTAHAN DALAM PERATURAN DAERAH KABUPATEN TANAH DATAR NOMOR 4 TAHUN 2008 TENTANG NAGARI - Lili Suryana; Ulya Atsani (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
The main problem in this thesis is how to implement the main tasks and functions of the head of affairs in the Nagari Simawang government and how to review Islamic constitutional law on the implementation of the main tasks and functions of the head of affairs in the Nagari Simawang government. The purpose of this discussion is to find and describe the implementation of the main duties and functions of the head of affairs in the government of Nagari Simawang and to find out and describe the review of Islamic constitutional law on the implementation of the main tasks and functions of the head of affairs in the government of Nagari Simawang. The type of research that the author uses is field research (field research). Based on the research that the author did, it was found that, several functions carried out by the Head of Government Affairs in Tanah Datar Regency Number 4 of 2008 regarding Nagari had not run effectively because there were several functions that were less effective, namely the function of providing services to the community in the field of land / land. agrarian affairs in accordance with applicable laws and regulations and in the function of assisting tasks in the field of collecting land and building taxes.